GAMBARAN NORMA SUBJEKTIF PADA WANITA USIA SUBUR UNTUK DETEKSI DINI KANKER SERVIKS METODE IVA - Thasa Azzahra; Sri Utami; Erika Erika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Some people have a trend to follow other people's views about their behavior. The people’s views about this action will affect them to belief in early detection of cervical cancer using IVA test. The purpose of this research is to identify the subjective norm at women in Rejosari Public Health Center, Tenayan Raya District, Pekanbaru City. This research used a quantitative descriptive design. The research sample were 60 respondents who were taken based on the inclusion criteria using purposive sampling technique. Data collection using a questionnaire that has been tested for validity and reliability. The analysis used is univariate analysis. The result of this research is there were 38 respondents who had low subjective norm (63.3%), 32 respondents had low subjective norm (36.7%). Overall, it can be concluded that the description of the subjective norm of women of childbearing age for early detection of cervical cancer using the IVA method is statistically high majorityKeywords: cervical cancer, IVA, subjective norm